Chicken albumen-based whispering gallery mode microlasers. Issue 39 (10th September 2020) - Mai, Hanh Hong; Nguyen, Tam Trong; Giang, Khoi Manh; Do, Xuan Tien; Nguyen, Toan T.; Hoang, Hieu Chi; Ta, Van Duong
Abstract : Chicken albumen-based biological microlasers are fabricated and these biolasers can work in the air, water and human serum. Abstract : Microlasers based on biomaterials have attracted enormous interest because of their promising potential for future applications in medical treatments, bio-tracking, and biosensing. In this work, we demonstrate chicken albumen as a novel and excellent low-cost biomaterial for a laser cavity. By using a simple but effective emulsion process, rhodamine B-doped chicken albumen microspheres with various diameters ranging from 20 μm to 100 μm can be fabricated. Under optical pulse excitation, these microspheres emit lasing emission. The lasing mechanism is investigated and ascribed to the whispering gallery mode (WGM). A threshold of 23.2 μJ mm −2 and a high Q -factor of approximately 2400 are obtained from an 82 μm-diameter microsphere. Size-dependent lasing characteristics are also examined, and the result shows good agreement with the WGM theory. Interestingly, these microsphere biolasers can operate in aqueous and biological environments such as water and human blood serum, which makes them a promising candidate for laser-based biosensing and biological applications.